Semiclassical quantization of M5 brane probes wrapped on AdS3 × S 3 and defect anomalies - M. Beccaria; L. Casarin; A. A. Tseytlin (Journal of High Energy Physics)
Abstract We consider two supersymmetric M5 brane probe solutions in AdS7 × S 4 and one in AdS4 × S 7 that all have the AdS3 × S 3 world-volume geometry. The values of the classical action of the first two M5 probes (with S 3 in AdS7 or in S 4) are related to the leading N 2 parts in the anomaly b-coefficient in the (2,0) theory corresponding to a spherical surface defect in symmetric or antisymmetric SU(N) representations. We present a detailed computation of the corresponding one-loop M5 brane partition functions finding that they vanish (in a particular regularization). This implies the vanishing of the order N 0 part in the b-anomaly coefficients, in agreement with earlier predictions for their exact values. It remains, however, a puzzle of how to reproduce the non-vanishing order N terms in these coefficients within the semiclassical M5-brane probe setup.